(untitled) (Acta Scientiarum. Health Sciences, 2016)
The aim of this study was to assesses the factors associated with the occurrence of urinary incontinence (UI) in elderly people living in long-term care homes. Reports on Urinary Incontinence coupled to clinical-functional and socio-demographic data were retrieved from the medical records of elderly people. In addition, the application of the protocols: Mini-Mental State Examination, Katz Index, Short Physical Performance Battery. It was considered a significance level of 5%. It was noted that the UI occurred in 80.6% of elderly people, with average age 76.5 years (± 8.3) and average time at the care home reaching 5.2 years (± 6.4). Significant UI association was reported with gender, education and disease. A discrete increase in scores occurred in protocols for elderly people without UI occurrence. It is concluded that sample was characterized by elderly females with less than five years living in homes. The elderly with UI were similar to elderly people in general with regard to protocols.